Global war on terror : Bangladesh perspective - Osmany, Mufleh R.; Kabir, Mohammad Humayun (Academic Press and Publishers Library in association with Bangladesh Institute of International and Strategic Studies, 2007)
Papers presented at the Seminar on Global War on Terror: Bangladesh Perspective, held in Dhaka, Bangladesh in 2007; organized by Bangladesh Institute of International and Strategic Studies.